High versus low ligation of inferior mesenteric artery during laparoscopic radical resection of rectal cancer: A retrospective cohort study. Issue 12 (March 2020) - You, Xiaolan; Liu, Qinghong; Wu, Jian; Wang, Yuanjie; Huang, Chuanjiang; cao, Gan; Dai, Jiawen; Chen, Dehu; Zhou, Yan
Abstract : Abstract: Laparoscopic radical resection is standard treatment for resectable rectal cancer. However, whether high or low inferior mesenteric artery (IMA) ligation should be performed remains controversial. This retrospective cohort study compared the advantages and disadvantages of low vs high IMA ligation in patients undergoing laparoscopic total mesorectal excision for rectal cancer. Rectal cancer patients (n = 322) undergoing total mesorectal excision at our institution in 2010 to 17 were enrolled; 174 underwent high IMA ligation group and 148 low IMA ligation (LIMAL group). Baseline data on patients, operative indices, economic indices, pathology findings, perioperative complications, and survival in the 2 groups were analyzed retrospectively. The low IMA ligation group had significantly higher anus retention ratio ( P  = .022), shorter hospital stay ( P  = .025), lower medical expenses ( P  = .032), fewer cases of anastomotic leakage ( P  = .023) and anastomotic stricture ( P  < .001), and lower incidence of postoperative genitourinary dysfunction ( P  = .003). Cox regression analysis indicated that local recurrence, distant metastasis, tumor differentiation, and tumor-node-metastasis stage were independently associated with survival. Low ligation of the IMA during laparoscopic radical resection of rectal cancer appears to be associated with a lower risks for anastomotic leakage, anastomotic stricture, and genitourinary dysfunction, a shorter hospital stay, and lower costs. In contrast, the rate of lymph node harvest, tumor recurrence rate, metastasis, or mortality was not found to be related with the level of IMA ligation.